Studies of photosensitivity and photo-induced negative differential resistance (NDR) of TIPS-pentacene-poly(3-hexyl)thiophene blend organic thin film transistor - Mansouri, S.; Jouili, A.; El Mir, L.; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2015)
We have simulated the experimental characteristics of the organic thin film transistor to reproduce the transfer and output characteristics in saturation regime. The photoresponse and gate field dependence of the charge transport characteristics of the TFTs were studied. The threshold voltage exhibited a positive shift from 0.34V in darkness to 5.18 V under illumination, which can be attributed to the well-known photovoltaic effect resulting from the transport of photogenerated holes and trappings of photogenerated electrons near the source electrode in organic phototransistors. When white light irradiated the organic TFTs, a negative differential resistance (NDR) behavior appears in the saturation region of output characteristics. This NDR behavior in TFTs can be explained in terms of trappings and releasing mechanism of the mobile charges in the interface between the electrodes (source and drain) and the organic layer. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: TIPS:P3HT-TFF; Photoresponse; Electrical properties; NDR effect